Application of compression test in analysis of mechanical and color changes in grapefruit juice powder as related to glass transition and water activity - Telis, V. R. N. [UNESP]; Martinez-Navarrete, N. (Elsevier B.V., 2010)
Physicochemical and structural properties of grapefruit juice powder were studied as affected by water activity. Powdered juice was obtained by freeze-drying and equilibrated at different water vapor pressure atmospheres in order to give samples with water activity in the range of 0-084 The mechanical properties of the powder were measured by confined compression tests and the compressed samples, which presented uniform surface and thickness, were subjected to color analysis The maximum force attained during the compression tests and the color coordinates could be quantified with good reproducibility. The results were related to water activity and to glass transition temperature The occurrence of mechanical changes in the powder was shown to precede significant color changes with increasing water activity. Considering the susceptibility to stickiness, the stability limit was observed at T-T(g) approximate to 2 degrees C, with a high degree of mechanical changes being detected at T-Tg 16 degrees C, whereas for significant color changes this critical temperature difference was around 32 degrees C (C) 2009 Elsevier Ltd All rights reserved
Keywords: Water content; Sorption isotherm; Stickiness; Freeze drying